2003
DOI: 10.1128/jb.185.7.2112-2121.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein with Phosphoglycerate Mutase Activity from the Archaeon Sulfolobus solfataricus

Abstract: When soluble extracts of the extreme acidothermophilic archaeon Sulfolobus solfataricus were incubated with [␥-32 P]ATP, several proteins were radiolabeled. One of the more prominent of these, which migrated with a mass of ϳ46 kDa on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), was purified by column chromatography and SDS-PAGE and subjected to amino acid sequence analysis via both the Edman technique and mass spectroscopy. The best match to the partial sequence obtained was the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…tomato and B. phymatum STM815 (this study) to be an obligate enzyme for both glycolysis and gluconeogenesis. dPGM enzymes have previously been identified in some bacteria, such as Haemophilus influenzae (Fleischmann et al, 1995), Streptomyces coelicolor (White et al, 1992) and Zymomonas mobilis (Yomano et al, 1993), whereas only the iPGM enzymes are found in archaea (Graham et al, 2002;Potters et al, 2003). Surprisingly, both dPGM and iPGM are also found in some bacteria, such as E. coli and Bacillus subtilis, although only one form is predominantly active (Fraser et al, 1999;Watabe & Freese, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…tomato and B. phymatum STM815 (this study) to be an obligate enzyme for both glycolysis and gluconeogenesis. dPGM enzymes have previously been identified in some bacteria, such as Haemophilus influenzae (Fleischmann et al, 1995), Streptomyces coelicolor (White et al, 1992) and Zymomonas mobilis (Yomano et al, 1993), whereas only the iPGM enzymes are found in archaea (Graham et al, 2002;Potters et al, 2003). Surprisingly, both dPGM and iPGM are also found in some bacteria, such as E. coli and Bacillus subtilis, although only one form is predominantly active (Fraser et al, 1999;Watabe & Freese, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, it is not uncommon that only a portion of the peaks in the mass spectrum derived from an in situ tryptic digestion of what appeared to be a single polypeptide spot or band from an electrophoretic gel can be traced to a single ORF (43). The extreme sensitivity of contemporary mass spectrometers renders them capable of detecting peptides from other, relatively minor species that might be present in the section of gel that was analyzed.…”
Section: Vol 186 2004mentioning
confidence: 99%
“…This proposed mechanism is in agreement with the finding that the characterized iPGAM from Sul. solfataricus autophosphorylates at this conserved serine residue (215).…”
Section: Phosphoglycerate Kinasementioning
confidence: 99%